Global, regional, and national trends in opioid analgesic consumption from 2015 to 2019: a longitudinal study. (April 2022) - Ju, Chengsheng; Wei, Li; Man, Kenneth K C; Wang, Zixuan; Ma, Tian-Tian; Chan, Adrienne Y L; Brauer, Ruth; Chui, Celine S L; Chan, Esther W; Jani, Yogini H; Hsia, Yingfen; Wong, Ian C K; et al.
Summary: Background: Previous studies have reported an extremely unbalanced global access to opioid analgesics. We aimed to determine contemporary trends and patterns of opioid analgesic consumption at the global, regional, and national levels. Methods: We analysed the global pharmaceutical sales data of 66 countries or regions from the IQVIA-Multinational Integrated Data Analysis System database on opioid analgesics between 2015 and 2019. Opioid analgesic consumption was measured in milligram morphine equivalent per 1000 inhabitants per day (MME per 1000/day). The global, regional, and national trend changes were estimated using linear regressions. Factors associated with consumption patterns and trend changes were explored in multivariable linear regression analyses. Findings: Overall opioid analgesic sales in the 66 countries or regions increased from 27·52 MME per 1000/day (16·63–45·54) in 2015 to 29·51 MME per 1000/day (17·85–48·79) in 2019 (difference per year 3·96%, 95% CI 0·26 to 7·80). Sales reduced yearly in North America (–12·84%; 95% CI –15·34 to –10·27) and Oceania (–2·96%; –4·20 to –1·70); increased in South America (28·69%; 7·18 to 54·53), eastern Europe (7·68%; 3·99 to 11·49), Asia (5·74%; 0·61 to 11·14), and western and central Europe (1·64%; 0·52 to 2·78); and did not differ in Africa or central America and the Caribbean. The global opioid consumption patterns were associated with country-level Human Development Index (p=0·040), cancer death rate excluding leukaemia (p=0·0072), and geographical location (p<0·0001). In 2019, opioid analgesic consumption ranged from 0·01 MME per 1000/day to 5·40 MME per 1000/day in the 17 countries and regions in the lowest consumption quartile, despite high income levels and cancer death rates in some of them. Interpretation: Global opioid analgesic consumption increased from 2015 to 2019. The trend changes were distinctive across regions, which could reflect the different actions in response to known issues of opioid use and misuse. Disparities in opioid analgesic consumption remained, indicating potential inadequate access to essential pain relief in countries with low consumption. Funding: None.